2003
DOI: 10.1038/nature02029
|View full text |Cite
|
Sign up to set email alerts
|

Language-tree divergence times support the Anatolian theory of Indo-European origin

Abstract: Languages, like genes, provide vital clues about human history. The origin of the Indo-European language family is "the most intensively studied, yet still most recalcitrant, problem of historical linguistics". Numerous genetic studies of Indo-European origins have also produced inconclusive results. Here we analyse linguistic data using computational methods derived from evolutionary biology. We test two theories of Indo-European origin: the 'Kurgan expansion' and the 'Anatolian farming' hypotheses. The Kurga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
564
2
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 759 publications
(600 citation statements)
references
References 25 publications
23
564
2
11
Order By: Relevance
“…3A). This pattern is largely expected, and the position of Greek as the outlier of IE in our sample agrees with previous computational experiments on lexical datasets (Bouckaert et al, 2012, Gray and Atkinson, 2003). …”
Section: Resultssupporting
confidence: 92%
“…3A). This pattern is largely expected, and the position of Greek as the outlier of IE in our sample agrees with previous computational experiments on lexical datasets (Bouckaert et al, 2012, Gray and Atkinson, 2003). …”
Section: Resultssupporting
confidence: 92%
“…Using similar methods, Gray and Jordan (2000) found that the distribution of 77 Austronesian languages was most consistent with a single common ancestral form in Taiwan which rapidly spread through the region, and Gray and Atkinson (2003) found evidence supporting the theory that the Indo-European language group was associated with the spread of agriculture from Anatolia around 8,000 to 9,500 years ago.…”
Section: Macroevolutionmentioning
confidence: 72%
“…Among the Indo-European languages, the words for two, three, five, I, and who each form a single cognate set across the entire language family: Every Indo-European language speaker has used a related sound for each of these meanings. Given that Indo-European probably arose as a language family about 8,000 years ago (Gray & Atkinson 2003), this translates into rates of evolution (Pagel 2000) as low as that of some genetic elements.…”
Section: Mark Pagelmentioning
confidence: 99%
“…Support for individual nodes on the tree can be tested using bootstrap analysis, or in the case of Bayesian phylogenetic inference, by estimating posterior probabilities of each node. Language groups analysed using phylogenetic methods include Indo-European [4,24], Austronesian [2] and Bantu [3]. The results of these studies indicate that linguistic data sets are as tree-like as are biological data sets of morphological or molecular characters, at least in their basic vocabulary (standard 100-or 200-word lists of conservative, cross-culturally universal meanings such as 'woman' and 'moon').…”
Section: Cultures As Speciesmentioning
confidence: 98%
“…In addition, phylogenetic methods use an explicit optimality criterion to choose among trees, and enable branch lengths to be calculated that are proportional to the number of changes (innovations) per branch. Some phylogenetic methods offer the possibility of estimating dates for ancestral nodes on the tree [29], and the tree can be calibrated using archaeological dates, as seen in a recent study supporting the agricultural origins of IndoEuropean in the 8th millennium BP [24]. In spite of these strengths, any tree remains a hypothesis about past relationships among taxa.…”
Section: Cultures As Speciesmentioning
confidence: 99%